Quaternary Structure, Salt Sensitivity, and Allosteric Regulation of β-AMYLASE2 From Arabidopsis thaliana - Monroe, Jonathan D.; Pope, Lauren E.; Breault, Jillian S.; Berndsen, Christopher E.; Storm, Amanda R. (Frontiers in Plant Science, 2018)
The β-amylase family in Arabidopsis thaliana has nine members, four of which are both plastid-localized and, based on active-site sequence conservation, potentially capable of hydrolyzing starch to maltose. We recently reported that one of these enzymes, BAM2, is catalytically active in the presence of physiological levels of KCl, exhibits sigmoidal kinetics with a Hill coefficient of over 3, is tetrameric, has a putative secondary binding site (SBS) for starch, and is highly co-expressed with other starch metabolizing enzymes. Here we generated a tetrameric homology model of Arabidopsis BAM2 that is a dimer of dimers in which the putative SBSs of two subunits form a deep groove between the subunits. To validate this model and identify key residues, we generated a series of mutations and characterized the purified proteins. 1) Three point mutations in the putative subunit interfaces disrupted tetramerization; two that interfered with the formation of the starch-binding groove were largely inactive, whereas a third mutation prevented pairs of dimers from forming and was active. 2) The model revealed that a 30-residue N-terminal acidic region, not found in other BAMs, appears to form part of the putative starch-binding groove. A mutant lacking this acidic region was active and did not require KCl for activity. 3) A conserved tryptophan residue in the SBS is necessary for activation and may form -bonds with sugars in starch. 4) Sequence alignments revealed a conserved serine residue next to one of the catalytic glutamic acid residues, that is a conserved glycine in all other active BAMs. The serine side chain points away from the active site and towards the putative starch-binding groove. Mutating the serine in BAM2 to a glycine resulted in an enzyme with a Vmax similar to that of the wild type enzyme but with a 7.5-fold lower KM for soluble starch. Interestingly, the mutant no longer exhibited sigmoidal kinetics, suggesting that allosteric communication between the putative SBS and the active site was disrupted. These results confirm the unusual structure and function of this widespread enzyme, and suggest that our understanding of starch degradation in plants is incomplete.